It’s geopolitics, stupid: explaining Russia’s Ukraine policy - Elias Götz (Контуры глобальных трансформаций: политика, экономика, право, 2018)
What lies behind Russia’s annexation of Crimea and its confrontational policies towards Ukraine? This article challenges the widely held perspective that President Putin’s personality and his security-service background is the central driver of Russia’s Ukraine policy. Instead, it puts forward a geopolitical explanation that emphasizes three factors: Ukraine’s geographic location; the EU’s increased activism in Eastern Europe; and the pro- western orientation of the new government in Kiev. Together, these three factors provide Russia with a strong incentive to pursue an assertive policy towards Ukraine. Moscow’s main aim is to regain some control over Kiev’s foreign policy orientation and, if that is not possible, to establish a belt of pro-Russian provinces in Ukraine’s east. The findings of this article suggest, moreover, that the West ’s current policies towards Russia are ineffective and potentially counterproductive. A major readjustment is urgently needed.